KORELASI PERSEPSI DAN MINAT DENGAN HASIL BELAJAR SISWA KELAS 10 LINTAS MINAT BIOLOGI SMAN 1 AMBARAWA - Yesy Milda Paula Pratama; Retno Sri Iswari; Sri Ngabekti (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
Biology is one of the cross-interest subject that much demanded by high school students who take a specialization group of Social and Language studies, but the study result of biology is relatively low. This research aims to determine the correlation between: (1) perception with study result of biology; (2) interest with study result of biology; and (3) perception and interest with study result of biology together. The research was conducted at SMAN 1 Ambarawa, population and sample are all 10th grade students of Cross-Interest Biology Class in the academic year 2016/2017. The research used non experimental quantitative design with correlational analysis. The data collected in the form of data of student’s perception, interest, and study result of biology. Data of perception and interest obtained by instrument of psychological scale with likert model, whereas data of study result obtained from the student value of final exam in the odd semester. The research results showed that: (1) the value of rx1y=0,213 (low category) with the value of Sig. 0,014 0,05 at significance level of 5%; (2) the value of rx2y=0,159 (very low category) with the value of Sig. 0,070 0,05 at significance level of 5%; and the value of R=0,216 (low category) with the value of Sig. 0,048 0,05 at significance level of 5%. Based on the research can be concluded that: (1) there is low positive correlation between perception with study result of biology; (2) there is no correlation between interest with study result of biology; and (3) there is low positive correlation between perception and interest with study result of biology together for 10th grade students of Cross-Interest Biology Class at SMAN 1 Ambarawa.